Motivating altruism: a field study - Nicola Lacetera; Mario Macis (Institute for the Study of Labor (IZA), 2008)
This paper analyzes the effects of a legislative provision that grants a one-day paid leave of absence to blood donors who are employees in Italy. The analysis is based on a unique dataset with the complete donation histories of the blood donors in an Italian town. The cross-sectional variation in job market status and type of employers, and job switching over time by a subset of donors, are the sources of variation we employ to study whether donors are responsive to the paid-day-off incentive in the choice of their donation days, and in the frequency of their donations. Our results indicate that economic considerations do affect blood donation decisions, for donors donate in days of the week that, given the day-off benefit, maximize their material returns in terms of consecutive days off work. We also find evidence, however, consistent with heterogeneous motivations in different donors, since a subset of donors systematically do not take advantage of the material reward. Finally, we find that the day-off privilege leads donors who are employees to make, on average, one extra donation per year. We discuss the implications of our findings for policies aimed at increasing the supply of blood, and more generally for incentivizing pro-social behavior.
urn:nbn:de:101:1-20081126251
Keywords: D12; 330; Incentives; altruism; public good provision; pro-social behavior; public health; Blutspende; Ökonomischer Anreiz; Urlaub; Altruismus; Soziales Verhalten; Feldforschung; Italien